2008
DOI: 10.1515/jbcpp.2008.19.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Some changes in carbohydrate metabolism during acclimation to moderate hyperthermic environment in rats

Abstract: We studied the influence of heat acclimation (1 to 48 h and 4 to 60 d at 35 +/- 1 degrees C) on certain hepatic carbohydrate-related enzymes and substrates in rats. The results showed a decrease of liver glycogen content and GPho-ase a activity during the period of short-term exposure, followed by normalization to the control level and stabilization to the new level in the period of long-term heat acclimation. Conversely, G-6-P-ase and F-1,6-BP-ase activities increased during the short-term period, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Besides the well-known hepatic glycogenolysis in the STHA [6][7][8], we also observed intensive glycogenolysis at the level of heart Glk stores (Fig. 1).…”
Section: Short-term Heat Acclimationsupporting
confidence: 63%
See 2 more Smart Citations
“…Besides the well-known hepatic glycogenolysis in the STHA [6][7][8], we also observed intensive glycogenolysis at the level of heart Glk stores (Fig. 1).…”
Section: Short-term Heat Acclimationsupporting
confidence: 63%
“…In this sense, there is an enhancement of the metabolic machinery to elevate the energy potential of heat-acclimated organism which is accompanied by a decrease of the rate of the whole body metabolism [4,5]. Metabolic changes which are most evident during heat acclimation are: energy sparing, which is manifested as a rebound of liver glycogen (Glk) in rats [6][7][8] and hamsters [9] (as a result of increased activity of enzymes involved in a direct Glk synthesis), and decreased glucose (Glu) production [6][7][8]. As is the case with the liver, heat acclimation produces favorable adaptations in mechanical and metabolic aspects of the heart performance, such as: twofold greater heart Glk level, increased b-adrenergic sensibility, lowered heart rate and greater stroke volume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that working muscles are the main source of endothermy (153,169) leading to fatigue and hyperthermic failure during severe heat stress, our knowledge of the impact of cross-adaptation on skeletal muscle is very limited. Young et al (245) indicated that heat acclimation lowers the aerobic metabolic rate and blood lactate accumulation during exercise in both cool and hot environments, but not at the expense of the greater glycogen reserves [noted in skeletal and cardiac muscles of adapted and cross-adapted humans and animals, (43,44,141,245)]. Lorenzo et al (126) demonstrated that active heat acclimation improves performance in temperate/cool environments and attributed this to adaptations in the vascular bed and changes in plasma volume.…”
Section: Skeletal Vs Cardiac Muscle Acclimation To Heat and Exercisementioning
confidence: 99%
“…could be summarized in three phases: short-term heat exposure (1 to 24 h) with intensive glycogenolysis and gluconeogenesis to glucose; a period with temporary changes (24 h to 7 d) with tendency of normalization to control level, and prolonged heat acclimation (7 d to 60 d), which favours both direct and indirect glycogen synthesis [20].…”
Section: Discussionmentioning
confidence: 99%